Impact of prior knowledge, rhetoricalpatterns,and gender differences on readingcomprehension of Iranian EFL students / Maryam Jalilehvand - Jalilehvand, Maryam (2014)

(untitled)
According to the schema theory, reading comprehension involves interaction between a text and a reader. This interaction involves the reader’s prior knowledge of the subject on the one hand, and the rhetorical structure of the text on the other hand. Therefore, the current study examines the impact of three independent variables (prior knowledge, rhetorical pattern, and gender) on students’ reading comprehension. In Iran, many high school students have difficulty in comprehending reading texts. Their L2 reading comprehension scores indicate that they are not performing well. Many studies have been done to investigate the influence of some factors on reading comprehension. However, the influences of prior knowledge, rhetorical pattern, and gender differences on reading comprehension simultaneously have been neglected. Guided by this view, this study is an attempt to examine the simultaneous impact of prior knowledge, rhetorical pattern, and gender on reading comprehension through detailed analysis of 232 high school major students. Statistical analysis including three-way ANOVA was applied on the collected data. The sample consists of 72 male and 160 female students from high schools in Savojbolagh County in Iran. The participants are from the same level of proficiency. Using a between-subjects design, participants were divided into eight groups. For each of four groups of readers (females and males), two texts had familiar content with description or causation pattern, and two other texts had unfamiliar content with description or causation pattern. Each group was asked to recall the text and finish a cloze test after reading each of the four passages. Recall protocols (recall of idea units and importance level) and cloze test were used as the measures of reading comprehension. Both recall protocol and cloze test analysis revealed that participants displayed better recall of the familiar text than the unfamiliar text, which suggests that prior knowledge has a facilitating effect on reading comprehension. Moreover, like many previous researches, this study found that the rhetorical pattern had a significant effect on recall. The comparison of means and standard deviations between groups at each level indicated that the students benefited more by causative text than by descriptive text. The results showed that prior knowledge and rhetorical pattern were two strong predictors of performance. Gender did not have a significant effect on subjects’ comprehension except for v the cloze test. In the light of two-way interaction effect between variables, there was also a statistically significant interaction effect between prior knowledge and gender. More interestingly, the results of the three-way ANOVA indicated that there was not any statistically significant interaction effect between prior knowledge, rhetorical pattern, and gender. In other words, the findings showed that a two-way interaction between prior knowledge and rhetorical pattern was not moderated by gender. Overall, this study suggests that prior knowledge and rhetorical pattern are two critical variables which may improve students’ reading comprehension. These results have practical implications in the EFL and ESL fields. Moreover, this research makes recommendations for further research on EFL reading.